Search for supersymmetry in pp collisions at sqrt[s]=1.96 TeV Using the trilepton signature for chargino-neutralino production. - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; et al. (2008)
We use the three lepton and missing energy trilepton signature to search for chargino-neutralino production with 2.0 fb;{-1} of integrated luminosity collected by the CDF II experiment at the Tevatron pp[over ] collider. We expect an excess of approximately 11 supersymmetric events for a choice of parameters of the mSUGRA model, but our observation of 7 events is consistent with the standard model expectation of 6.4 events. We constrain the mSUGRA model of supersymmetry and rule out chargino masses up to 145 GeV/c;{2} for a specific choice of parameters.